2001
DOI: 10.1080/10584600152647092
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Political Talk Radio On Political Attitude Formation: Exposure Versus Knowledge

Abstract: The effects of political news on the mass audience are usually difficult to establish empirically. Recent models of mass communication effects have held that political knowledge is a better indicator of media reception than traditional measures of exposure. This claim is tested in two studies of attitudes toward Democratic and Republican leaders during the 1996 U.S. presidential primary campaigns. The impact of messages from three types of political talk radio (PTR) is examined: Rush Limbaugh, other conservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…In particular, studies have found a relationship between one-sided programming and attitudes toward political parties and public policies. For example, people who listen to one-sided radio programming supporting the Republican Party, such as The Rush Limbaugh Show, were more likely to hold negative attitudes toward Democrats and positive attitudes toward Republicans (Barker & Knight, 2000;Lee & Cappella, 2001). Research has shown similar results for attitudes toward public policies, such as healthcare (Barker, 1998).…”
Section: One-sided Media Message Consumption and Attitudinal Ambivalencesupporting
confidence: 58%
See 1 more Smart Citation
“…In particular, studies have found a relationship between one-sided programming and attitudes toward political parties and public policies. For example, people who listen to one-sided radio programming supporting the Republican Party, such as The Rush Limbaugh Show, were more likely to hold negative attitudes toward Democrats and positive attitudes toward Republicans (Barker & Knight, 2000;Lee & Cappella, 2001). Research has shown similar results for attitudes toward public policies, such as healthcare (Barker, 1998).…”
Section: One-sided Media Message Consumption and Attitudinal Ambivalencesupporting
confidence: 58%
“…Research has revealed a range of important democratic effects of consuming one-sided political media (Barker, 1998;Barker & Knight, 2000;Lee & Cappella, 2001). In particular, studies have found a relationship between one-sided programming and attitudes toward political parties and public policies.…”
Section: One-sided Media Message Consumption and Attitudinal Ambivalencementioning
confidence: 98%
“…The grassroots nature of call-ins Downloaded by [University of California Santa Barbara] at 02:06 26 August 2015 lends trust to the credibility of the source and the economic costs are minimal. This in turn can inform public opinion; for instance, Lee and Cappella's study of Limbaugh listenership found that audiences' agreement with one-sided messages on PTR increases with greater exposure to those positions (Lee & Cappella, 2001). The shaping of political attitudes fuels the political legitimacy necessary for elites to pursue a course of action.…”
Section: Political Talk Radio and Political Mediamentioning
confidence: 96%
“…Studies of PTR around the world have studied what citizens say on air (Crittenden, 1971;Gunster, 2008;Lee, 2002;O'Sullivan, 2005;Surlin, 1986) and levels of audience exposure (Bennett, 2002). A considerable body of work has examined listening effects on interpretation of the news (Hall & Cappella, 2002;Lee & Cappella, 2001), effects on audience political attitudes and voting behavior (Barker, 2002;Yanovitzky & Cappella, 2001), and effects on the political efficacy of listeners (Hofstetter & Gianos, 1997;Hofstetter et al, 1994;Ross, 2004). Scholarly attention has thus been paid Downloaded by [University of California Santa Barbara] at 02:06 26 August 2015 to citizen callers, to syndicated program hosts such as Rush Limbaugh, and to the outward effects of political talk radio.…”
Section: Political Talk Radio and Political Mediamentioning
confidence: 99%
“…Barker, 1998aBarker, , 1999Barker & Knight, 2000;Bolce, deMaio, & Muzzio, 1996;Hall & Cappella, 2002;Holbert, 2004;Hollander, 1996;Jones, 1998Jones, , 2002Owen, 1997Owen, , 2000Pfau et al, 1997;Yanovitzky & Cappella, 2002). Underlying this research effort is the Asian Journal of Communication 79 belief that radio talk shows, when compared with traditional news media, provide the conditions for relatively powerful media effects (Barker, 1998a;Lee & Cappella, 2001;Owen, 2000). First, talk radio is not a journalistic medium bounded by the norms of objectivity and neutrality.…”
Section: The Political Significance and Influence Of Talk Radiomentioning
confidence: 98%